Analisis Pemikiran Ekonomi Islam Muhammad Baqir Sadr: Studi Literatur Sistematis terhadap Konsep dan Implementasinya - Syahbuddin Dalimunthe, Razi Azwar (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Various global economic crises and the need for a more just economic system, Sadr's thinking has become very relevant to be reviewed. However, there is still a gap in the academic literature regarding a systematic analysis of his economic thinking, especially in the context of its practical implementation in the modern era. Apart from that, the majority of studies on Islamic economics in Indonesia focus more on Sunni thinkers, while the contributions of thinkers such as Sadr receive less attention. This research examines the Islamic economic thought of Muhammad Baqir al-Sadr through a systematic analysis of his works, with a focus on three main aspects: (1) methodological analysis of key concepts in his economic thought, (2) exploration of his criticism of the conventional economic system, and (3) study of contributions to Islamic economics especially "Iqtisaduna". Using a qualitative methodology with a literature study approach, this research aims to identify, analyze and evaluate Sadr's fundamental contribution to the development of Islamic economics. The research results show that Sadr's thinking offers a comprehensive framework that integrates Islamic values with modern economic principles, providing a viable alternative to conventional economic systems.